2023
DOI: 10.1021/acs.nanolett.3c00391
|View full text |Cite
|
Sign up to set email alerts
|

Self-Optimized Ligand Effect of Single-Atom Modifier in Ternary Pt-Based Alloy for Efficient Hydrogen Oxidation

Abstract: Modifying the atomic and electronic structure of platinum-based alloy to enhance its activity and anti-CO poisoning ability is a vital issue in hydrogen oxidation reaction (HOR). However, the role of foreign modifier metal and the underlying ligand effect is not fully understood. Here, we propose that the ligand effect of single-atom Cu can dynamically modulate the d-band center of Pt-based alloy for boosting HOR performance. By in situ X-ray absorption spectroscopy, our research has identified that the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…Currently, Pang et al designed a ternary alloy with the single atom Cu dispersed in PtPd alloy (PtPdCu 1 /C). [56] By in-situ X-ray absorption spectroscopy, the potential-driven structural rearrangement of Cu single atoms from original fivecoordination configuration (5c-PtPdCu 1 /C) to higher eightcoordination configuration (8c-PtPdCu 1 /C) (Figure 5a) strengthens the ligand effect in PtPdCu 1 /C and thereby accelerates the charge redistribution of Pt and Pd. As a result, the d-band center of Pt and Pd in PtPdCu 1 /C was modulated, generating proper HBE/OHBE (Figure 5b-c) and reduced CO adsorption energies (Figure 5d) for expediting the HOR kinetics and the anti-CO poisoning ability.…”
Section: Single-atom Alloysmentioning
confidence: 98%
See 1 more Smart Citation
“…Currently, Pang et al designed a ternary alloy with the single atom Cu dispersed in PtPd alloy (PtPdCu 1 /C). [56] By in-situ X-ray absorption spectroscopy, the potential-driven structural rearrangement of Cu single atoms from original fivecoordination configuration (5c-PtPdCu 1 /C) to higher eightcoordination configuration (8c-PtPdCu 1 /C) (Figure 5a) strengthens the ligand effect in PtPdCu 1 /C and thereby accelerates the charge redistribution of Pt and Pd. As a result, the d-band center of Pt and Pd in PtPdCu 1 /C was modulated, generating proper HBE/OHBE (Figure 5b-c) and reduced CO adsorption energies (Figure 5d) for expediting the HOR kinetics and the anti-CO poisoning ability.…”
Section: Single-atom Alloysmentioning
confidence: 98%
“…(d) CO adsorption energy of Pt/C, PtPd/C, 5c-PtPdCu 1 /C, and 8c-PtPdCu 1 /C; inset: computed CO adsorption configuration on Pt/C, PtPd/C, 5c-PtPdCu 1 /C, and 8c-PtPdCu 1 /C (H: white; C: gray; O: red; Cu: orange; Pd: purple; Pt: blue). Reproduced from ref [56]. Copyright (2023), with permission from American Chemical Society.…”
mentioning
confidence: 99%
“…While extensive research has been dedicated to identifying suitable catalyst materials over an extended period, comprehending catalytic mechanisms through the lens of surface science offers a systematic approach. Traditionally, noble metals such as Pt have been recognized as prominent catalysts, capitalizing on their ability to furnish a substantial active area to reactants and mitigate catalyst deactivation. Nevertheless, the formation of bimetallic catalysts has revealed their potential to significantly outperform existing noble metal catalysts due to the distinctive occurrence of atomic interfaces. , This encompasses alloy types that influence electronic characteristics by altering atomic arrangements, as well as phase-separation types where distinct phases can synergistically or organically undertake roles through independent spatial segregation. Despite numerous experimental findings showcasing heightened catalytic activity in heterogeneous compounds, there remains a scarcity of quantitative or experimental discussions addressing the optimization and regulation of the underlying electronic properties driving this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…The K edge XANES spectra reveal that the edge energy of Ru/Ru x Fe 3– x O 4 falls within the range between Ru foil and RuO 2 , indicating a cationic valence state (Figure d). A positive shift in the rising edge energy of Ru/Ru x Fe 3– x O 4 compared with that of Ru foil signifies increased Ru valence states, which can be attributed to the transmission of charges from Ru to interfacial oxide, leading to charge rearrangement at the heterointerfaces. , Furthermore, the Fourier-transformed EXAFS (FT-EXAFS) spectrum and wavelet transform (WT) contour plots provide additional evidence of the contributions of Ru–Ru and Ru–O bonds in Ru/Ru x Fe 3– x O 4 (Figure e,f). The estimated coordination numbers of Ru–Ru and Ru–O bonds are 2.53 and 3.37, respectively (Table S2), indicating that the catalyst possesses the unsaturated coordination of Ru species. , Meanwhile, the EXAFS spectra of Ru/Ru x Fe 3– x O 4 and Fe 3– x O 4 show a similar or slightly expanded scattering distance compared with that of Fe 3 O 4 (Figure g), which suggests that their Fe average valence state is close to +2.67.…”
mentioning
confidence: 96%
“…Recently, nanometer size metal catalysts have shown excellent activity in energy-related reactions because of the low average metal–metal coordination number compared with those of large nanoparticles. , Nevertheless, stabilizing metal clusters during electrocatalytic processes remains challenging due to the absence of a restraining force against aggregation . Interestingly, it has been widely demonstrated that encapsulating metal sites with different supports can significantly enhance catalytic performance through strong metal–support interaction (SMSI). Among support materials, FeO x possesses abundant surface active sites, accelerating the hydrolytic dissociation kinetics on surfaces and water molecule decomposition. , Meanwhile, the synergistic effect between clusters and metal oxides can regulate the energy band structure and Fermi level at the catalyst interface, which optimize the adsorption and desorption of intermediate substances in specific steps. , Also, the synergistic effect can enhance the catalyst stability by forming an alloy or composite structure during the precipitation reaction to increase the resistance against corrosion and poisoning. …”
mentioning
confidence: 99%